Enhanced Single Cavity Soliton Generation in Kerr Microresonators Via Inverse-Kelly Sideband - Mingle Liao; Heng Zhou; Yong Geng; Yun Ling; Baojian Wu; Kun Qiu (IEEE Photonics Journal, 2017)
The formation of dissipative cavity solitons in microresonators provides an efficient process for ultrashort pulse synthesis and mode-locking of Kerr frequency combs. However, as dissipative cavity solitons arise spontaneously from a continuous-wave pump, deterministically controlling the number of intracavity solitons remains challenging to date. In this paper, we propose an efficient yet easy way to access single cavity soliton formation in microresonators via inverse-Kelly sideband generation in Kerr comb spectrum. Our method only requires fixed-speed unidirectional pump frequency sweeping to achieve single soliton state, avoiding complex pump scanning trajectory and high frequency pump modulation. Moreover, we report on the determinacy of single-soliton generation using the proposed method; statistic analysis shows that excellent determinacy as high as 98.7% is achieved.